Un remarquable professeur de l’ancienne Université de Vilnius, François Norvaiša (1742—1819) - Žemaitis, Z. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:З. Жемайтис. Выдающийся профессор математики Старого Вильнюсского университета Франциск Норвайша (1742—1819)Z. Žemaitis, Įžymusis Vilniaus Senojo universiteto profesorius Pranciškus Norvaiša (1742—1819)